A CASE OF RELAPSING-REMITTING TUMEFACTIVE MULTIPLE SCLEROSIS. (29th November 2012) - Turnbull, H; Karsan, N; Hogg, F; Pereira, A
Abstract : A 23-year-old left-handed female developed progressive right arm weakness and expressive dysphasia. She had papilloedema and right-sided UMN facial palsy, arm weakness and positive Babinski reflex. MRI brain demonstrated a 7.7 cm diameter heterogeneously enhancing mass lesion with surrounding vasogenic oedema lying within the left posterior frontal lobe with associated midline shift. CSF contained unmatched oligoclonal bands, consistent with a diagnosis of tumefactive multiple sclerosis. She was treated with IV methylprednisolone with complete recovery. Three years later she presented with dizziness, visual disturbance and cognitive deficits. On examination, she had a left homonymous hemianopia and a Gerstmann-like syndrome. She rapidly deteriorated with left-sided weakness, neglect, hemisensory loss, aphasia and dysphagia. MRI demonstrated an acute, demyelinating plaque of 7.2 cm involving the right parieto-occipital white matter and posterior frontal white matter with mass effect. Repeat CSF examination showed unmatched oligoclonal bands. She was treated with intravenous methylprednisolone and plasma exchange and dramatically improved. She is continuing her inpatient rehabilitation. Tumefactive lesions in MS usually convert to typical relapsing-remitting disease on recurrence. Here we present a rare case of relapsing-remitting tumefactive disease which has only previously been reported once in the literature. We have demonstrated a good response to immunosuppressive and immunomodulatory therapy.